Effect of Ethanol Extract of Terminalia catappa on Serum Reproductive Hormones in Poloxaimer Induced Hypercholesterolemic Female Wistar Rats - K, Dasofunjo; C, Nyeche S.; O, Ogar B.; O, Emuru E.; O, Owu D.; O, Ugbada M.; B, Odu F.; N, Ogar U. (African Journal of Biochemistry and Molecular Biology Research, 2024)
This research work was carried out to access the effect of ethanol extract of Terminalia catappa, on sexual hormones in poloxamer induced hypercholesterolemia in Wistar rats. Thirty- five (35) Wistar female rats were allowed to acclimatize for a period of 7 days, in a well-ventilated room at room temperature and relative humidity of 29°C and 70% respectively with 12 hours natural light-dark cycle. They were allowed food and water ad libitum. Good hygiene was maintained by daily cleaning and removal of faeces and spills from their cages. The rats were randomly divided into 5 groups of 7 rats each. Group A: was fed with normal chow and distilled water (NC). Group B: was induced with 1.0g/kg dose of P-407 without treatment (HC). Group C: was induced with 1.0g/kg dose of P-407 and treated with atorvastatin (ATV) at 20mg/kg body weight, Group D: was induced with 1.0g/kg dose of P-407 and treated with leaves extract (HLE) at 100mg/kg body weight, Group E: was induced with 1.0g/kg dose of P-407 and treated with leaf extract (HLE) at 200mg/kg body weight/ day for 14days .The dose regimens were administered once daily for the period of the study. The rats were monitored for clinical signs and death. The result reveals that there was a significant (P<0.05) increase in serum oestrogen, progesterone, follicle stimulating hormone (FSH), and luteinizing hormone (LH) when compared with the normal, standard and hyperlipidemic control. Contrastingly, there was a significant decrease (P< 0.05) in serum testosterone and prolactin (PRL) when compared to the normal and standard control. It can be inferred from this present research work that the extract may stimulate or regulate ovulation or promote sexual health and or drive possibly due to the presence of phytonutrient or phytoandrogens.